2015
DOI: 10.2903/sp.efsa.2015.en-724
|View full text |Cite
|
Sign up to set email alerts
|

Review of the state of the art of human biomonitoring for chemical substances and its application to human exposure assessment for food safety

Abstract: Human biomonitoring (HBM) measures the levels of substances in body fluids and tissues. Many countries have conducted HBM studies, yet little is known about its application towards chemical risk assessment, particularly in relation to food safety. Therefore a literature search was performed in several databases and conference proceedings for 2002 -2014. Definitions of HBM and biomarkers, HBM techniques and requirements, and the possible application to the different steps of risk assessment were described. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 186 publications
0
50
0
1
Order By: Relevance
“…the internal dose) that results from complex pathways of human exposure and also incorporates toxicokinetic information and individual characteristics such as a genetically based susceptibility (10). It takes into account processes such as metabolism, bioaccumulation and excretion (7). Through the use of biomarkers it is not only possible to monitor exposure but it also becomes feasible to detect early health effects (10).…”
Section: Added Value and Advantages Of Human Biomonitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…the internal dose) that results from complex pathways of human exposure and also incorporates toxicokinetic information and individual characteristics such as a genetically based susceptibility (10). It takes into account processes such as metabolism, bioaccumulation and excretion (7). Through the use of biomarkers it is not only possible to monitor exposure but it also becomes feasible to detect early health effects (10).…”
Section: Added Value and Advantages Of Human Biomonitoringmentioning
confidence: 99%
“…HBM relies on the use of biomarkers, measurable indicators of changes or events in biological systems. Biomarkers are measurements of the concentrations of chemical substances, their metabolites or reaction products in human tissues or specimens such as blood, urine, hair, adipose tissue, teeth, saliva, breast milk, and sperm (7).…”
Section: Introductionmentioning
confidence: 99%
“…Human biomonitoring can identify vulnerable groups and can reduce the assumptions regarding consumption rates (Choi et al, 2015). Results of epidemiological studies on mycotoxins using biomonitoring have been reported in the past two decades (Duarte et al, 2012;Ediage et al, 2013;Gilbert et al, 2001;Pena et al, 2006;Rubert et al, 2011;Turner et al, 2010;Van der Westhuizen et al, 2011).…”
Section: Characteristicsmentioning
confidence: 99%
“…food, inhalation, skin contact) and reflects the internal biological active fraction (Choi et al, 2015). The exposure can be assessed by converting urinary mycotoxin concentrations to intake levels, taking into account their kinetics, such as rate of excretion (i.e.…”
Section: Human Biomonitoring Studiesmentioning
confidence: 99%
“…A review of the state of the art of human bio-monitoring for chemical substances and its application to human exposure assessment for food safety (Choi et al, 2015) was published as an EFSA supporting publication. The report provides a review of the results obtained from human bio-monitoring studies and concludes that human bio-monitoring allowed for the identification of emerging chemicals or chemical classes of possibly higher exposed sub-groups or specific vulnerable groups of a population and of other issues relevant for EFSA's risk assessment activities.…”
Section: Methods Developmentmentioning
confidence: 99%